The impact of language and high-stakes testing policies on elementary school English language learners in Arizona. - Wright, Wayne E.; Choi, Daniel (Education Policy Analysis Archives, 2006)
This article reports the results of a survey of third-grade teachers of English Language Learners (ELLs) in Arizona regarding school language and accountability policies—Proposition 203, which restricts bilingual education and mandates sheltered English Immersion; the federal No Child Left Behind Act of 2001 (NCLB); and Arizona LEARNS, the state’s high-stakes testing and accountability program. The instrument, consisting of 126 survey questions plus open-ended interview question, was designed to obtain teacher’s views, to ascertain the impact of these polices, and to explore their effectiveness in improving the education of ELL students. The survey was administered via telephone to 40 teacher participants from different urban, rural and reservation schools across the state. Each participant represents the elementary school in their respective school district which has the largest population of ELL students. Analyses of both quantitative and qualitative data reveal that these policies have mostly resulted in confusion in schools throughout the state over what is and is not allowed, and what constitutes quality instruction for ELLs, that there is little evidence that such policies have led to improvements in the education of ELL students, and that these policies may be causing more harm than good. Specifically, teachers report they have been given little to no guidance over what constitutes sheltered English immersion, and provide evidence that most ELL students in their schools are receiving mainstream sink-or-swim instruction. In terms of accountability, while the overwhelming majority of teachers support the general principle, they believe that high-stakes tests are inappropriate for ELLs and participants provided evidence that the focus on testing is leading to instruction practices for ELLs which fail to meet their unique linguistic and academic needs. The article concludes with suggestions for needed changes to improve the quality of education for ELLs in Arizona.